2021
DOI: 10.1007/s11528-021-00626-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers to Teach in K-12 Blended Environments: A Systematic Mapping Review of Research Trends, Impact, and Themes

Abstract: Despite evidence concerning the widespread growth of K-12 blended teaching and the impact that emergency remote teaching during the COVID-19 pandemic has had on the spread of K-12 online and blended teaching, we could find no systematic reviews focused on preparing K-12 teachers for blended teaching. Previous literature reviews, such as those from Halverson et al. ( 2012 ) and Drysdale et al. ( 2013 ), have noted the lack of research focused on K-12 blended teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 61 publications
1
14
0
2
Order By: Relevance
“…A sudden increase started in 2019, and the interest in blended learning reached a peak by 2020 and 2021. This time trend matches that reported by Spring and Graham (2017) andShort et al (2021). The peak coincided with the Coronavirus…”
supporting
confidence: 91%
See 1 more Smart Citation
“…A sudden increase started in 2019, and the interest in blended learning reached a peak by 2020 and 2021. This time trend matches that reported by Spring and Graham (2017) andShort et al (2021). The peak coincided with the Coronavirus…”
supporting
confidence: 91%
“…Furthermore, the reviews conducted by Drysdale et al (2013) and Spring and Graham (2017) confirmed that most of the research has focused on higher education settings, showing less interest in K-12 settings. Short et al (2021), in their study, examined blended learning research in the K-12 context and reported that while the number of publications increased by the second decade of the 2000s, the number of articles focusing on blended learning in the K-12 context was relatively lower compared to the number of articles focusing on the subject in the higher education context. Halverson et al (2014) highlighted in their study that there was a lack of theoretical cohesiveness in blended learning research, while Drysdale et al (2013) noted that most of the blended learning research is approached through a distance education-related theoretical lens (e.g., Community of Inquiry, Transactional Distance, Community of Practice, Transformational Learning Theory, etc.).…”
Section: Related Studiesmentioning
confidence: 99%
“…Moreover, stakeholders could formulate policies that support teachers to acquire technological and pedagogical skills that could lead them to be adapted to a new era. An era in which teachers should be ready to use digital tools in teaching various subject matters in-person or/and online (Short et al 2021). Therefore, now more than ever, the educational policy should organize training programs focused on teaching using specific technologies in specific ways (Lavidas et al 2021, Theodoropoulou et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, "blended teaching" (Short et al 2021) seems to be for preschool teachers' an important part of the ongoing teaching practices that they choose today in their effort to transform and integrate digital learning activities into front-line teaching activities. The process of transforming and adapting new teaching practices is a broader process based on the ability to find, access and use information, and on interacting with other users and navigating the Internet and ICT environment safely and responsibly, starting mainly from respecting the rights of students to provide them with many, different and essential learning experiences (UNESCO 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several recent reviews of online and blended learning, particularly discussing 'emergency remote learning' as during the pandemic. Some of these discuss emergency situations (Barbour et al, 2020;Crompton et al, 2021;Hodges et al, 2020), some the management of school closures, changes in pedagogy and preparation for teachers (Bond, 2020a;Bond et al, 2021;Short et al, 2021;Viner et al, 2020), some vulnerable students and those with mental health issues (Drane et al, 2020;Nearchou et al, 2020) and some the implications for policy (Darmody et al, 2020).…”
Section: Recent Perspectivesmentioning
confidence: 99%